Scrub Typhus Presenting as Acute Undifferentiated Febrile Illness in a 12-Year-Old Child from Northeast India: A CaseReport (Indian Journal of Case Reports, 2026)
Scrub typhus is an important cause of acute undifferentiated febrile illness in children residing in endemic regions ofIndia. Its diagnosis is often challenging because of non-specific clinical manifestations and the absence of classicalsigns such as eschar. We report the case of a 12-year-old boy from Northeast India who presented with persistent highgrade fever, generalized weakness, and reduced oral intake. Clinical examination revealed mild bilateral pedal edemawithout rash, eschar, hepatosplenomegaly, or neurological abnormalities. Initial empirical treatment with intravenousceftriaxone failed to produce significant clinical improvement. Further evaluation demonstrated elevated inflammatorymarkers and positive Scrub Typhus Immunoglobulin M serology, confirming the diagnosis. The child was treated withintravenous doxycycline 65 mg twice daily, followed by oral doxycycline, resulting in rapid defervescence and markedclinical recovery within 48 h. This case highlights the importance of maintaining a high index of suspicion for scrubtphus in children presenting with prolonged fever in endemic areas, even in the absence of classical clinical findings.Early diagnosis and timely initiation of doxycycline therapy are essential for preventing severe complicationandensuringfavorableoutcomes.